Weaving meanings from the deliberative process of collegiate management in nursing - Giovana Dorneles Callegaro Higashi; Alacoque Lorenzini Erdmann (Universidade de São Paulo, 2014)
OBJECTIVE: to understand the meanings of the collegiate deliberations attributed by its members on an undergraduate nursing course.METHOD: Grounded Theory, interviews being held with 30 participants, making up 4 sample groups, between January and June 2012, in a public higher education institution.RESULT: 5 categories emerged, indicating the phenomenon and weaving the paradigmatic model: Understanding the experience of the complex relationships and interactions in the deliberations of collegiate management in nursing: intertwining divergences, convergences, dialogs, collectivities and diversities. This deliberative process presents various meanings involving discussion, and divergent, convergent and complementary positions, through dialog, commitment and negotiation.CONCLUSION: the deliberations in the collegiate of nursing, intertwining dialogs, collectivities and diversities, mold the complex relational fabrics.